Prevention of Anemia with Iron in Adolescent Girls - Zaitun, Zaitun; Farid Rivai, Ahmad (Jurnal Medisci, 2024)
This study looked at whether iron supplementation has a role in keeping teenage girls from becoming anemic. Anemia is characterized by a reduction in hemoglobin levels, erythrocyte count, and hematocrit, which impairs the ability of circulating hemoglobin levels and erythrocytes to supply oxygen to bodily tissues. Anemia affects 50–80% of people worldwide. Anemia is more common in teenage girls (15–19 years old) than it is in fertile women (26.9%). Adolescent females are highly susceptible to anemia, which a number of reasons, such as inadequate iron intake, menstruation, and food, can cause. The body needs iron, a micronutrient, to produce hemoglobin. The literature review research technique starts with topic selection and moves on to keyword analysis, with the two keywords being iron and anemia. From 2017 to 2021, articles can be found using Indonesian through the following e-resource databases: Perpusnas, PMC, Ebsco, ProQuest, Mendelay, and Google Scholar. Thirty-four journals were excluded, leaving 111 journals for assessment. The results indicated that iron tablets were utilized in five articles, while additional guava fruit juice, vitamin C, folic acid, and protein were used in two articles. One study indicated that tempeh could raise adolescent girls' hemoglobin levels before and after the intervention, helping prevent anemia. The efficacious delivery of iron can effectively avert anemia. One way to lower the prevalence of anemia is to prevent it by eating foods high in iron and administering blood-added tablets (TTD).